2021
DOI: 10.1186/s40729-021-00323-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical considerations for medication-related osteonecrosis of the jaw: a comprehensive literature review

Abstract: Background Medication-related osteonecrosis of the jaw (MRONJ), which was first reported as bisphosphonate-related osteonecrosis of the jaw (BRONJ) in bisphosphonate users, is a rare but severe soft and hard tissue disease induced by several types of medications. There has been a deluge of information about MRONJ, such as epidemiology, risk factors, clinical recommendations for dental treatment to prevent it, and treatment strategies in medication-prescribed users. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 76 publications
2
75
0
5
Order By: Relevance
“…The current literature suggests various treatment strategies for MRONJ depending on its stage and other clinical parameters of the patient [3,6,11,22]. Despite non-surgical treatment options, the surgical approach is still considered the best treatment choice of MRONJ [10,12,13,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature suggests various treatment strategies for MRONJ depending on its stage and other clinical parameters of the patient [3,6,11,22]. Despite non-surgical treatment options, the surgical approach is still considered the best treatment choice of MRONJ [10,12,13,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…While these drugs are used to treat bone metastases and osteoporosis, these have been affecting the quality of life related to oral health, Refs. [1,[4][5][6] making daily dental treatment more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of patients with advanced cancer treated with either zoledronic acid or denosumab, found 13/155 (8.4%) developed MRONJ, which was significantly associated with the number of infusions and the duration of antiresorptive therapy [12]. A recent literature review and meta-analysis including 13,857 patients reported the prevalence of MRONJ after receiving zoledronic acid for cancer ranged from 0.4-1.6% after one year, 0.8-2.1% after two years, and 1.3-2.3% after three years, with greater incidence after more years of administration [13]. ONJ incidence secondary to denosumab therapy ranged from 0.5% to 2.1% after one year, 1.1-3.0% after two years, and 1.3-3.2% after three years of treatment [13].…”
Section: Incidencementioning
confidence: 99%
“…A recent literature review and meta-analysis including 13,857 patients reported the prevalence of MRONJ after receiving zoledronic acid for cancer ranged from 0.4-1.6% after one year, 0.8-2.1% after two years, and 1.3-2.3% after three years, with greater incidence after more years of administration [13]. ONJ incidence secondary to denosumab therapy ranged from 0.5% to 2.1% after one year, 1.1-3.0% after two years, and 1.3-3.2% after three years of treatment [13].…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation